К вопросу периодизации и хронологии верхнего палеолита бассейна Десны - Чубур, А.А. (Археологія, 1996)
В статье предлагается хронологическая схема для верхнего палеолита бассейна Десны и ee обоснование. Знание хронологического распределения памятников позволяет сделать некоторые выводы о расселении человека эпохи верхнего палеолита в Подесенье. На базі стратиграфії й геохронології для верхнього палеоліту Десни виділяються чотири хронологічні групи пам'яток -- ранньоосташківська, гмелинська, часу максимального похолодання та часу пост максимуму. Просторово-часовий аналіз розподілу пам'яток свідчить, що заселеність території зменшувалась під час похолодання та зростала у періоди потеплінь, що особливо яскраво фіксується у північній частині регіону. Упродовж верхнього палеоліту змінюється й осілість населення — у період пост максимуму вона знижується, що, можливо, пов'язано з несталим кліматом, та, як наслідок, посиленням міграцій на гіпотетичному рівні можна простежити міграції окремих груп населення, зокрема носіїв традицій типу Тимонівка-Юдиново. Four chronological groups of relics: the Early Stashkovskaya, the Gmelinskaya, the cold spell maximum time, and the post-maximum period — are picked out based on stratigraphy and a geo-chronology for the Upper Paleolithic period in the Desna River Basin Area. The spatial-temporal analysis of a monument’s distribution shows, that the population of the territory decreased in time of the cold snap and increased at the periods of getting warmer. This feature is especially pronounced in the Northern part of the region. During the Upper Paleolithic period, a settled way of life of the population was changed too. At the post-maximum period it was decreased, what, in probable, is connected with an unstable climate and, as a consequence, with an intensification of migration. At level of hypothesis the migration of separate population groups, in particular the carriers of traditions of such a type as Tymonovka-Judinovo, may be followed.